PENGARUH PENGGUNAAN MEDIA INTERNET TERHADAP MINAT BELAJAR SISWA DI SMK MUHAMMADIYAH 02 PEKANBARU - Yulia Novita (P3M STKIP 'Aisyiyah Riau, 2017)
This study aims to determine the effect of internet media use on students' interest in learning at SMK Muhammadiyah 02 Pekanbaru. This research was conducted at SMK Muhammadiyah 02 Pekanbaru with a population of 130 students and 60 samples were taken using the Taro Yamane formula using simple random sampling method. Data analysis used simple linear regression. The linear line equation Y = 1.569 + 0.544 X. From the simple linear regression results there is a positive and significant effect. The determinant coefficient of the analysis is 0.915, meaning that the influence of the use of internet media will cause an increase in student interest in learning by 91.5%. While the remaining 8.5% is influenced by other variables not included in this study. To test the hypothesis in this study tested with t test regression, obtained t count = 5.369 with a significance level of 0.000. By using a significance limit of 0.05, the significance value is greater than the 5% level, which means that Ho is rejected and Ha is accepted. Thus, the hypothesis individually / partially variable internet media has an influence on student interest in learning.